Adopsi Varietas Unggul Kacang Hijau di Sentra Produksi - Trustinah Trustinah; B. S. Radjit; N. Prasetiaswati; Didik Harnowo (Iptek Tanaman Pangan, 2014)
Mungbean varieties possessing characteristics of early maturing (55-65 days), drought tolerance, and adaptive on less fertile soil, are considered as having good potential to be developed in the sub-optimal farm lands. The other advantage of growing mungbean, it is complementary with rice nutrition, by which rice protein is enriched by a rich mungbean lysine. At the farm level, mungbean can improve farmers’ nutritions and income. Mungbean crop in Indonesia covers 297,315 ha with the total production of 341,342 ton and the productivity of 1.15 t/ha. The mungbean production centers include Central Java, East Java, West Nusa Tenggara, South Sulawesi, West Java and East Nusa Tenggara, where they contribute around 91.7 percent to the national production. Variety is a component technology which is easily adopted and safe for the environment. Planting high yielding mungbean varieties had proven to increase the grain productivity in most areas. Types of varieties preferred by farmers varied among regions. The availability of many high yielding mungbean varieties, therefore, allow farmers to select the most suitable ones for their environment. However, not all released varieties had been planted by farmers. The choices of mungbean varieties among farmers generally consider the productivity, consumer preference, and the grain price. Some farmers prefer mungbean with dull seed color while other prefers glossy large or small seeds. The mungbean varieties with small seed, commonly is used for beansprouts. Several mungbean high yielding varieties had been adopted in the farming system of the production centers. Introduction of new varieties with seed characteristics preferred by farmers, followed by demostration plots, and the seed are to be produced by local seed producers are strategy for accelerating the adoption of new varieties.